Perkembangan Model Pembelajaran Berbasis Permainan Sirkuit Dalam Meningkatkan Motorik Halus Anak Usia 4-6 Tahun - Putri Elisabeth Kolly; Elsa Mariana Pian; Oktifina Loni Sabila; Sifra Yulti Nisipeni; Desi Katarina Saepito; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Fine motor skills are an important aspect of early childhood development through active and enjoyable learning. This study aims to analyze the effect of a circuit-based learning model on the fine motor skills of children aged 4–6 years at Efrata Preschool. The study used a quantitative approach with an ex post facto design. The sample size was 20 children aged 4–6 years, selected using a total sampling technique. Data collection was conducted using a questionnaire consisting of a circuit-based learning model scale and a child's fine motor skills scale that met validity and reliability tests. The data were analyzed using simple linear regression analysis using SPSS version 25.0. The results showed that the circuit-based learning model had a positive and significant effect on the fine motor skills of children aged 4–6 years (p = 0.003 < 0.05). The coefficient of determination (R Square) of 0.381 indicates that the circuit-based learning model contributed 38.1% to children's fine motor development, while the remaining 61.9% was influenced by factors outside the study. Thus, implementing a circuit-based game-based learning model in a structured and consistent manner can be an alternative learning method to optimize fine motor development in early childhood education (PAUD) units.